Perubahan Kepribadian Penderita Stroke dan Kecemasan pada Caregiver Stroke - Daulay, Nanda Masraini (Universitas Aufa Royhan, 2022)
Stroke sufferers are unable to independently meet their daily needs, most have difficulty controlling their emotions. Changes in the personality of stroke sufferers are one of the complaints that are often conveyed by caretakers or caregivers of stroke sufferers. The aim of this study is to find out the description of changes in the personality of stroke patients and anxiety to caregivers in the work area of ​​the Sihepeng Mandailing Natal Health Center in 2021. The research design is descriptive with cross-sectional approach. The population in this study were caregivers of 29 stroke sufferers. The sampling technique in this study was total sampling so that a total sample of 29 people was obtained. The results showed that 19 respondents (65.5%) had positive personality changes and 48.3% (14 respondents) had no anxiety in the anxiety category. This study recommends that caregivers be able to have a positive effect in providing care and be able to accept personality changes that occur in stroke sufferers. All family members must be able to provide positive support to each other so that the stroke patient feels better so that anxiety does not occur in the caregiver.